Tari Wadian Dadas Bawo: Eksistensi dan Upaya Pelestarian di Generasi Milenial - Clara, Titha Widya; Romadoni, Muhamad (Tambuleng, 2025)
Indonesia is a country rich in cultural diversity, especially traditional arts that serve as the identity of each ethnic group. In Central Kalimantan, particularly East Barito Regency, there is a distinctive dance called Tari Wadian Dadas Bawo. This dance holds significant meaning and function in the life of the Dayak Ma’anyan community, especially in traditional healing rituals and customary ceremonies such as weddings. This study aims to examine the existence of Tari Wadian Dadas Bawo among the millennial generation and its preservation efforts. The research uses qualitative methods with a field study approach, observations, in-depth interviews with artists and community members, and document analysis. The results show that despite challenges posed by modernization and globalization, Tari Wadian Dadas Bawo remains existent and is continuously preserved through cultural festivals, art workshops, and dance studios. Support from local government plays a crucial role in attracting millennials to actively participate in preserving this cultural heritage. This study recommends continuing preservation efforts with cultural education strategies targeting young generations intensively.